Stable carbon isotopic evidence of methane consumption and production in three alpine ecosystems on the Qinghai–Tibetan Plateau - Kato, Tomomichi; Yamada, Keita; Tang, Yanhong; Yoshida, Naohiro; Wada, Eitaro (Atmospheric environment (1994), 2013)
To understand the mechanisms of soil CH4 consumption and production in alpine ecosystems, we for the first time examined the stable carbon isotope ratio of CH4 (δ13C–CH4) at three major grassland vegetation types, alpine meadow, alpine shrub, and alpine wetland, on the Qinghai–Tibetan Plateau. The alpine meadow and shrub showed net CH4 absorption in their vertical profiles of CH4 concentration in summer, but a difference in their processes. Whereas the alpine shrub was dominated by CH4 consumption in its soil profile, CH4 production in the alpine meadow could slightly cancel consumed CH4 in shallow soil from −0.3 to −0.1 m. This potential CH4 production can be attributed to the relatively wet soil type of that ecosystem, which might allow methanogenesis to act in moist soil lumps in the shallow layer. The alpine wetland differed in methane production, consumption, and transport pathways between hummock and hollow plots. In summer, both plots were enriched in 13C–CH4 in dissolved CH4 in soil pore water, suggesting that CH4 production was conducted mainly by acetate fermentation. In autumn, CH4 production was shifted toward CO2/H2 reduction. Furthermore, in hummocks, plant-mediated transport of CH4 by vascular plants appeared to perform passive CH4 flow from deep soil to atmosphere, which allowed the produced CH4 to bypass the oxidation zone in shallow soil. In hollows, however, CH4 produced in shallow soil was subject to simultaneous oxidation. The fractional oxidation rate on gross CH4 production in hollows was estimated by simple mass balance model at 7–17% in summer and 35–36% in autumn. •Stable carbon isotope ratio in soil CH4 was examined in alpine ecosystems in China.•Alpine meadow and shrub showed different fractionation factors in methane oxidation.•In alpine wetland, acetate fermentation was major contributor on methane production.•Hummocks showed plant-mediated transport of CH4 from deep soil to the atmosphere.•In hollows, fractional oxidation rate on methane production was estimated at 7–36%.